GhGPAT12/25 Are Essential for the Formation of Anther Cuticle and Pollen Exine in Cotton (Gossypium hirsutum L.) - Zhang, Meng; Wei, Hengling; Hao, Pengbo; Wu, Aimin; Ma, Qiang; Zhang, Jingjing; Wang, Hantao; Fu, Xiaokang; Ma, Liang; Lu, Jianhua; Yu, Shuxun (Frontiers in Plant Science, 2021)
Glycerol-3-phosphate acyltransferases (GPATs), critical for multiple biological processes like male fertility, have been extensively characterized. However, their precise functions and underlying regulatory mechanism in cotton anther development are unclear. This research demonstrated the importance of GhGPAT12/25 (a paralogs pair on A12/D12 sub-chromosome of cotton) to regulate the degradation of tapetum, anther cuticle formation and pollen exine development. GhGPAT12 and GhGPAT25 exhibited specifically detected transcripts in tapetum and pollen exine during the early anther developmental stages. GhGPAT12/25 are sn-2 glycerol-3-phosphate acyltransferases and can transfer the acyl group of palmitoyl-CoA to glycerol-3-phosphate (G3P). CRISPR/Cas9-mediated knockout identified the functional redundancy of GhGPAT12 and GhGPAT25. Knockout of both genes caused completely male sterility associated with abnormal anther cuticle, swollen tapetum, and inviable microspores with defective exine and irregular unrestricted shape. RNA-seq analysis showed that the loss-of-function of GhGPAT12/25 affects the processes of wax metabolic, glycerol monomers biosynthesis and transport. Consistently, cuticular waxes were dramatically reduced in mutant anthers. Yeast one-hybrid system (Y1H), virus-induced gene silencing (VIGS) and dual-luciferase (LUC) assays illustrated that GhMYB80s are likely to directly activate the expression of GhGPAT12/25. This study provides important insights for revealing the regulatory mechanism underlying anther development in cotton.